Security risk assessment and protection in the chemical and process industry. Issue 1 (24th May 2014) - Reniers, Genserik; Van Lerberghe, Paul; Van Gulijk, Coen
<x xml:space="preserve">Abstract</x> This article describes a security risk assessment and protection methodology that was developed for use in the chemical and process industries in Belgium. The method employs a risk‐based approach according to design principles for object‐oriented protection, using so‐called Typicals. The approach is beneficial for workers in the chemical industry because of the familiarity with safety models and concepts in this particular industry. The model combines the rings‐of‐protection approach with generic security practices including management and procedures, security technology (e.g., CCTV, fences, and access control), and human interactions (proactive as well as reactive). The method is illustrated in a case‐study where a practical protection plan was developed for an existing chemical company. This article demonstrates that the method is useful for similar chemical and process industrial activities far beyond the Belgian borders, as well as for cross‐industrial security protection. In summary, this article offers an insight into how the chemical sector might protect itself on the one hand and an insight into how security risk management may be practiced on the other hand. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 72–83, 2015